A Heterogeneous Hybrid Cloud Storage Service Using Storage Gateway with Transfer Acceleration and Diff Algorithm - Jamal Abdul Nasyir; Idris Winarno; Udin Harun Al-Rasyid (AI Society & STMIK Indonesia, 2022)
Recently, the cloud service has the potential to replace conventional cluster and grid systems. The objective of migrating apps to the cloud is to minimize maintenance and procurement expenses while simultaneously boosting scalability and availability. However, embra=cing cloud technology created some challenges, such as the complexity of cloud storage. In addition, many clients underestimate if it is not plug-and-play. Each vendor has its access methods, and nonstandard application programming interfaces (APIs) make integrated applications, such as archiving or sharing data with cloud storage, complicated, costly, and require high throughput. Furthermore, organizations did not have many alternatives for implementing high-performance object storage systems in the cloud and on-premises data centers until now. In this paper, we would like to suggest a storage gateway as a solution to this issue and will optimize it using Transfer Acceleration and Diff algorithms to improve the performance, Intelligent Tiering to reduce costs, and Server-Side encryption for extra protection. Moreover, utilizing Storage Gateway has proven can provide more efficient integration between the on-premises data center environment and the AWS Cloud Storage ecosystem that is safer and more reliable. This technology can work in a common data center environment regardless of the vendor used by the company it can communicate seamlessly with the AWS Environment.